The Use of Indigofera Indigofera zollingeriana (Miquel, 1855) Leaf Meal as Feed Raw Material for Growth of Hoven’s Carp Fry Leptobarbus hoevenii (Bleeker, 1851) - Agustina, Emilda; Santoso, Limin; Ediwarman, Ediwarman; Paino, Paino; Supono, Supono (Jurnal Perikanan dan Kelautan, 2023)
Indigofera leaf meal can be used as an alternative raw material and has high potential as a source of vegetable protein for Hoven’s carp fry to reduce the use of imported raw materials. The purpose of this study was to examine the effect of using indigofera leaf meal with different combinations of feed as feed raw materials on growth performance and survival of Hoven’s carp (Leptobarbus hoevenii) fry. This study was carried out from July to August 2021 at the freshwater aquaculture center (BPBAT) Sungai Gelam Jambi. This study method used a completely randomized design (CRD) with 3 treatments and 3 replications, i.e: control (commercial feed 100%), treatment 1 (commercial feed 50%+ indigofera leaf meal 50%), and treatment 2 (indigofera leaf meal 100%). The data obtained were analyzed by Anova and further tested by Duncan's test. Based on the analysis of variance, the use of Indigofera zollingeriana leaf meal had a significant effect (P<0.05) on absolute weight growth, absolute length, specific growth rate, and feed conversion ratio, while survival rates were not significantly different (P >0.05). The results showed that the increasing proportion of the use of indigofera leaf meal experienced a decrease in the growth performance of Hoven’s carp fry.